Multilayer Microstructure of Idiopathic Epiretinal Macular Membranes. Issue 6 (8th November 2017) - Azzolini, Claudio; Congiu, Terenzio; Donati, Simone; Passi, Alberto; Basso, Petra; Piantanida, Eliana; Mariotti, Cesare; Testa, Francesco; Caprani, Simona M.; Cattaneo, Jennifer; Vinciguerra, Riccardo
Purpose: To identify the ultramicroscopic structure of idiopathic epiretinal macular membranes (iEMMs) by scanning electron microscopy (SEM). Methods: We examined 28 iEMMs surgically removed from 28 eyes of 28 patients. All specimens, previously observed at stereomicroscope, were treated with an osmium maceration technique. Fine resolution of iEMMs' 3D architecture and their interaction with the retina were studied using a Philips SEM-FEG XL-30 microscope. Results: The specimens appeared as laminar connective structures partially or completely adherent to the inner limiting membrane (ILM). We identified 4 types of structures: (1 ) distinct layers of thin sheets of woven fibers; (2 ) folded layers of inhomogeneous thickness of fibrous material more consistent; (3 ) thicker and more rigid layers recognizable as collagen fibrils with typical 64-nm period, collagen fibrils isolated or intermingled between them; (4 ) lacunar structures with inflammatory and/or necrotic material. The first 3 types of structures appear to thicken towards a centripetal direction from the ILM to the vitreous in order from 1 to 3. The interface of ILM-iEMM tissue shows particular small bridges of connection. Cells are rarely found, especially in the tissue near the ILM. Conclusions: Layers of various materials follow one another in iEMMs. Cells are rarely found. The interface ILM-iEMM tissue shows particular small bridges of connection. The dynamic modeling of bended layers begins in soft tissue.